Pengaruh Isu-isu Lingkungan dan Merek dalam Kerangka Theory Planned Behavior terhadap Minat Beli Produk Ramah Lingkungan - Rezyanti Apriliani Harsono; Hepy Hefri Ariyanto; Pulung Peranginangin (Akademi Akuntansi YKPN Yogyakarta, 2023)
Indonesia is the second largest plastic contributor country.This study aims to analyze the effect of attitudes, environmental impact knowledge, brand familiarity, environmental awareness, brand involvement in social media and quality of information on purchase intention with green buying behavior as a moderating variable. The number of observations was 406. The analysis technique used to test the hypothesis was multiple regression analysis with SPSS 25 software and for the moderating test used the moderated regression analysis. The results showed that environmental awareness, brand involvement and quality of information had a significant positive effect on purchase intention. Brand familiarity and environmental impact knowledge had positive no significant effect and attitude had negative no significant. Green buying behavior is able to strengthen all variables other than brand familiarity which weakens the relationship to purchase intention.